ANTEROLATERAL THIGH FLAP: VERSATILITY AND ANATOMIC VARIATIONS - Iqbal, Tariq; Shah, Asif; Ajmal, Samira; Khan, Firdous (Journal of Postgraduate Medical Institute, 2011)
Objective: Introduction: Material and Methods: Results: Conclusion: Transmuscular perforators (mostly 3) were found in all the patients, commonly arising from descending branch of lateral circumflex femoral artery. Thirteen patients were operated and free microvascular anterolateral thigh flap was used. In 12 patients the main vascular supply was through the descending branch of the lateral circumflex artery (LCFA). One patient has a vascular supply through the transverse branch of the lateral circumflex femoral artery. Reconstruction of 13 composite defects in 13 consecutive patients by free microvascular anterolateral thigh flap at the Department of Plastic and reconstructive surgery, Hayatabad Medical complex, Peshawar. Antero lateral thigh flap has become one of the most commonly used flap for the reconstruction of various soft tissue defects. The anterolateral thigh flap is known for variations of its vascular pedicle. Its major limitation has been uncertainty in predicting perforator anatomy, with the occasional absence of suitable perforators and high variability in their size and course. To determine the pattern of the cutaneous perforator of the lateral circumflex femoral artery in anterolateral thigh perforator flap.